2006
DOI: 10.1158/1055-9965.epi-05-0837
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Instability in Barrett's Esophagus Is Related to Telomere Shortening

Abstract: Barrett's esophagus is a useful model for the study of carcinogenesis, as the metaplastic columnar epithelium that replaces squamous esophageal epithelium is at elevated risk for development of adenocarcinoma. We examined telomere length and chromosomal instability (CIN) in Barrett's esophagus biopsies using fluorescence in situ hybridization. To study CIN, we selected centromere and locus-specific arm probes to chromosomes 17/17p (p53), 11/11q (cyclin D1), and 9/9p (p16 INK4A), loci reported to be involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
53
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 50 publications
6
53
1
Order By: Relevance
“…Telomere dysfunction is also associated with bone marrow failure (50), specifically MGUS and multiple myeloma (51,52). Very short telomeres are also associated with CLL (53), dyskeratosis congenita (54), pancreatic cancer (55), prostate cancer (9), and Barrett's esophagus, which is associated with an increased risk of esophageal adenocarcinoma (56). These data suggest that the alteration of telomeres is potentially an important tool for cancer diagnostics for a broad range of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere dysfunction is also associated with bone marrow failure (50), specifically MGUS and multiple myeloma (51,52). Very short telomeres are also associated with CLL (53), dyskeratosis congenita (54), pancreatic cancer (55), prostate cancer (9), and Barrett's esophagus, which is associated with an increased risk of esophageal adenocarcinoma (56). These data suggest that the alteration of telomeres is potentially an important tool for cancer diagnostics for a broad range of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…T here have been ver y few re por ts of specific aneusomies in esophageal premalignant lesions; using FISH, some studies showed hyperdiploidy involving chromosomes 4 and 8 in BE, aneuploidy in chromosome 11 in esophageal tumors and Barrett's dysplasias [20][21][22][23] . In the present work, all the precancerous lesions including BE with high-grade dysplasia exhibited aneusomy of chromosome 11.…”
Section: Discussionmentioning
confidence: 99%
“…Short telomeres have also been found in biopsies taken from Barrett's esophagus, a pre-neoplastic state that precedes esophageal adenocarcinoma. Barrett's esophagus samples with the shortest telomeres also had the highest degree of chromosomal abnormalities (Finley et al, 2006). As a result, it is currently believed that many if not most cancers arise from cells in which telomere erosion has provoked a 'crisis' beyond which telomerase expression had to be reinstated (or alternative telomere maintenance mechanisms had to be activated) to immortalize the cells (Sahin and Depinho, 2010).…”
mentioning
confidence: 99%
“…Tetraploidization has been observed in the early stages of colorectal (Danes, 1978), breast (Dutrillaux et al, 1991), cervical cancer (Olaharski et al, 2006) as well as in Barrett's esophagus (Finley et al, 2006). Although the natural history of tetraploidy in human cancers has not been thoroughly investigated, in vitro results indicate that the inactivation of p53 is permissive for tetraploidization (because p53-sufficient cells usually die from apoptosis as they become tetraploid) (Castedo et al, 2006;Senovilla et al, 2009; Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation